Multi-colony tracking of a marine central place forager reveals a site specific yet broadly consistent foraging strategy - Jonathan M. Handley; Joshua C. Wilson; Norman Ratcliffe; Alastair M. M. Baylis; Sarah Crofts; Pierre A. Pistorius (Marine Biology, 2026)
Colonial central place foraging seabirds with a wide species range inhabit highly heterogenous habitats, which may result in colony-specific foraging behaviours. Simultaneously tracking seabirds from multiple colonies is key to elucidating factors influencing foraging behaviour and determining how species might respond to environmental perturbations. Here, we investigate the foraging behaviour of gentoo penguins ( Pygoscelis papua ) breeding at the Falkland Islands in relation to habitat availability and prey types. We examine the horizontal and vertical foraging distribution of 78 birds during two breeding seasons from three colonies, selected for their geographic separation and contrasting habitats. Through comparison of general foraging characteristics, we found that at each colony, penguins exhibited either pelagic foraging behaviour in the water column, or benthic foraging behaviour near to the sea floor. This was dictated by the surrounding bathymetry, with pelagic behaviour being associated with steeper surrounding slopes, and was in accordance with the known diet of birds. Then, using a hurdle model to predict dive intensity around each colony, we show that habitat suitability for all colonies declined once distance to the colony exceeded ~ 30 km, while other variables had differing influences. At different colonies, the use of either pelagic or benthic foraging behaviours suggests that gentoo penguins have the capacity to respond to variable environmental conditions. However, given that foraging trips only reached mean maximum distances of 23.1 km ± 12.2 km from the colony during the breeding season, marine spatial planning efforts need to protect inshore waters around critical gentoo penguin colonies to effectively conserve the species.

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Intentional take of seabirds for human consumption: a global review to inform conservation and policy needs for migratory species - Jonathan M. Handley; Joanne Morten; G. Barry Baker; Aline Küehl-Stenzel; Maximin K. Djondo; Graeme A. Taylor; Iván Ramirez; Heidrun Frisch-Nwakanma; Noëlle F. Kümpel; Tammy E. Davies (Biological Conservation, 2026)

Aluminium adjuvants and childhood health: a call for science - Guillemette Crépeaux; Jeremy R. Hammond; Jonathan B. Handley; Brian Hooker; Karl Jablonowski; Lluís Luján; James Lyons-Weiler; Marika Nosten-Bertrand; Christopher A. Shaw; Yehuda Shoenfeld; Lucija Tomljenovic; Christopher Exley (Journal of Trace Elements in Medicine and Biology, 2026)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Seabird and reef conservation must include coral islands - Tristan Berr; Maria P. Dias; Serge Andréfouët; Tammy Davies; Jonathan Handley; Matthieu Le Corre; Alexandre Millon; Éric Vidal (Trends in Ecology & Evolution, 2023)

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Gemma V. Clucas; Jane L. Younger; Damian Kao; Louise Emmerson; Colin Southwell; Barbara Wienecke; Alex D. Rogers; Charles‐André Bost; Gary D. Miller; Michael J. Polito; Patrick Lelliott; Jonathan Handley; et al. (Molecular Ecology, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here, we used a comparative framework and genomewide data obtained through RAD ‐Seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at‐sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor ( Aptenodytes forsteri ), king ( A. patagonicus ), Adélie ( Pygoscelis adeliae ) and chinstrap ( P. antarctica ) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins ( P. papua ) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at‐sea range and oceanography in species lacking genetic data.

Following Rapoport's Rule: the geographic range and genome size of bacterial taxa decline at warmer latitudes - Gavin Lear; Kelvin Lau; Anne‐Marie Perchec; Hannah L. Buckley; Bradley S. Case; Martin Neale; Noah Fierer; Jonathan W. Leff; Kim M. Handley; Gillian Lewis (Environmental Microbiology, 2017)
Summary We sought to test whether stream bacterial communities conform to Rapoport's Rule, a pattern commonly observed for plants and animals whereby taxa exhibit decreased latitudinal range sizes closer to the equator. Using a DNA sequencing approach, we explored the biogeography of biofilm bacterial communities in 204 streams across a ∼1000 km latitudinal gradient. The range sizes of bacterial taxa were strongly correlated with latitude, decreasing closer to the equator, which coincided with a greater than fivefold increase in bacterial taxonomic richness. The relative richness and range size of bacteria were associated with spatially correlated variation in temperature and rainfall. These patterns were observed despite enormous variability in catchment environmental characteristics. Similar results were obtained when restricting the same analyses to native forest catchments, thereby controlling for spatial biases in land use. We analysed genomic data from ∼500 taxa detected in this study, for which data were available and found that bacterial communities at cooler latitudes also tended to possess greater potential metabolic potential. Collectively, these data provide the first evidence of latitudinal variation in the range size distributions of freshwater bacteria, a trend which may be determined, in part, by a trade‐off between bacterial genome size and local variation in climatic conditions.

Jack of all prey, master of some: Influence of habitat on the feeding ecology of a diving marine predator - Jonathan M. Handley; Maëlle Connan; Alastair M. M. Baylis; Paul Brickle; Pierre Pistorius (Marine Biology, 2017)

A novel foraging strategy in gentoo penguins breeding at sub-Antarctic Marion Island - Tegan Carpenter-Kling; Jonathan M. Handley; David B. Green; Ryan R. Reisinger; Azwainewi B. Makhado; Robert J. M. Crawford; Pierre A. Pistorius (Marine Biology, 2017)

Kleptoparasitism in foraging gentoo penguins Pygoscelis papua - Jonathan M. Handley; Pierre Pistorius (Polar Biology, 2016)

Temporal variation in the diet of gentoo penguins at the Falkland Islands - Jonathan M. Handley; Alastair M. M. Baylis; Paul Brickle; Pierre Pistorius (Polar Biology, 2016)

Redox cycling of arsenic by the hydrothermal marine bacterium Marinobacter santoriniensis - Kim M. Handley; Marina Héry; Jonathan R. Lloyd (Environmental Microbiology, 2009)
Summary Marinobacter santoriniensis NKSG1 T is a mesophilic, dissimilatory arsenate‐reducing and arsenite‐oxidizing bacterium isolated from an arsenate‐reducing enrichment culture. The inoculum was obtained from arsenic‐rich shallow marine hydrothermal sediment from Santorini, Greece, with evidence of arsenic redox cycling. Growth studies demonstrated M. santoriniensis NKSG1 T is capable of conserving energy from the reduction of arsenate [As(V)] with acetate or lactate as the electron donor, and of oxidizing arsenite [As(III)] heterotrophically with oxygen as the electron acceptor. The oxidation of As(III) coincided with the expression of the aoxB gene encoding for the catalytic molybdopterin subunit of the heterodimeric arsenite oxidase operon, indicating the reaction is enzymatically controlled, and M. santoriniensis NKSG1 T is a heterotrophic As(III)‐oxidizing bacterium. Although it is clear that this organism also performs dissimilatory As(V) reduction, no amplification of the arrA arsenate reductase gene was attained using a range of primers and PCR conditions. Marinobacter santoriniensis NKSG1 T belongs to a genus of bacteria widely occurring in marine environments, including hydrothermal sediments, and is among the first marine bacteria shown to be capable of either anaerobic As(V) respiration or aerobic As(III) oxidation.